DNA damage in canine transmissible venereal tumor cells - Amaral, Anne Santos do; Ferreira, Isabelle [UNESP]; Colodel, Márcia Moleta [UNESP]; Salvadori, Daisy Maria Favero [UNESP]; Rocha, Noeme Sousa [UNESP] (My University, 2011)
The Transmissible Venereal Tumor (TVT) has been classified according to the predominant cell type as follows: lymphocytoid, plasmocytoid, and mixed. Various degrees of aggressiveness with large array of biological behaviour have been described according to the TVT cell lineages, the present study was designed to investigate the level of DNA damage in the three TVT cell types aiming a better understanding of mechanisms related to the aggressiveness of this neoplasia. A total of 35 dogs were evaluated, with no restriction regarding sex, age or breed, and with clinical and cytological diagnoses for TVT. Cell samples from the 35 tumoral neoplasmas were obtained by fine needle aspiration and taken to cytology and DNA damage analysis by the comet assay. From the 35 TVT cases, 12 (34.3%) were plasmocytoid, 11 (31.4%) lymphocytoid, and 12 (34.3%) mixed. Statistically significant (p<0.05) higher level of DNA damage was detected in lymphocytoid TVT cells when compared to the other two types.

O Tumor Venéreo Transmissível (TVT) tem sido classificado de acordo com o tipo celular predominante da seguinte forma: linfocitóide, plasmocitóide e misto. Vários graus de agressividade com grande variedade de comportamento biológico, têm sido descritos de acordo com as morfologias das células do TVT. O presente estudo teve como objectivo investigar o nível de danos no DNA nos três tipos de células do TVT, visando uma melhor compreensão dos mecanismos relacionados com a agressividade dessa neoplasia. Um total de 35 cães, sem restrição quanto à idade, sexo ou raça, e com diagnóstico clínico e citológico de TVT foram avaliados. Amostras de células foram obtidas a partir de 35 tumores, por aspiração com agulha fina, e realizada citologia e análise dos danos no DNA, pelo Ensaio Cometa. Dos 35 casos de TVT, 12 (34,3%) foram plasmocitóide, 11 (31,4%) linfocitóide, e 12 (34,3%) misto. Estatísticamente (p <0,05) o TVT linfocitóide apresentou maior nível de danos no DNA quando comparado com os outros dois tipos.